TANTANGAN DAN PELUANG PEMBIAYAAN KESEHATAN DI INDONESIA SEBUAH TINJAUAN LITERATUR - Dea Purnama Sari Sir; Siti Soraya Tambunan, Amelia Putri, Fitriani Pramita Gurning (Jurnal Kesehatan, 2024)
Health services are a public good, meaning that everyone must have access to them in order to have a chance of living a healthy life. The aim of this research is to understand the challenges faced in health financing in Indonesia. This type of research involves synthesizing, summarizing, and reviewing a number of previous studies to create a systematic review of the body of knowledge that has been published in online scientific journals. The results obtained between financing and the services they receive from hospitals are health development such as equitable access to health care and quality services (assured quality), so strong, stable and sustainable health financing is very important for health development and delivery of health services. To ensure adequate, fair, efficient and effective health funding, health policy reform in a country must place significant emphasis on health financing policies.